HODROVÁ, URBAN, MACURA – A POSTMODERN LOOK AT THE CZECH NATIONAL MYTH - Gawarecka, Anna (Porównania, 2015)
After the Velvet Revolution of 1989 the Czech literature, released from the duty of ideological commitment (both in its official version and dissident imperative of unmasking/accusing com-munistic deformation and repressions), faced the situation when hitherto – obvious from the times of National Revival – ideas of tasks and the important role of the writer lost their validity. This situation obliged the artists to reconsider their opinions about the position of writers in society and to reconstruct the system of the traditional myths and stereotypes which until then had defined the Czech collective identity. Their interest was naturally fixed on the beginning of the national project, which means the return to the times of forming the Revival imaginary struc-ture which is still up-to-date, although not dominating, in the area of the interpretation of the history and still influences the literary representation of the present day. In the novels of Vladi-mír Macura, Daniela Hodrová or Miloš Urban this imaginary structure is partly called in ques-tion and brought under the process of demythologization and multiplication of senses.